Surgical challenges and outcome of endoscopic endonasal approaches in the management of recurrent pituitary adenomas - Ahmed Nageeb Mohamed Taha (Romanian Neurosurgery, 2020)
Background: Various surgical approaches for the management of midline anterior skull base meningiomas exist in the literature. The main surgeon target is proper selection the appropriate approach that achieves total removal of the lesion without causing morbidity or mortality and facilitates safe effective removal of the tumor.